2018
DOI: 10.14202/vetworld.2018.1074-1081
|View full text |Cite
|
Sign up to set email alerts
|

Sources of contamination, prevalence, and antimicrobial resistance of thermophilic Campylobacter isolated from turkeys

Abstract: Aim:Sources of contamination, prevalence, and antimicrobial susceptibility of thermophilic Campylobacter isolated from turkey samples were determined.Materials and Methods:A total of 300 samples were collected from 3 farms (fecal droppings) and 4 poultry slaughterhouses (neck skins and ceca) located in the middle area of Algeria (Algiers, Boumerdès, and Bouira). After detection, an antibiogram was realized only for slaughterhouses samples.Results:Samples from cecum (90.0%, 90/100; 95% confidence interval (CI)=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In Algeria, Bouhamed, Bouayad, Messad, Zenia, Naim and Hamdi [77] found that Campylobacter was present in 55% of 100 turkey neck skins sampled from three traditional and one modern abattoir located in the country’s middle regions, Algiers, Bouïra, and Boumèrdes. The abattoirs were characterised by a lack of disinfection protocols and sterilisation of equipment, and by the use of dirty uniforms.…”
Section: Prevalence Of Campylobacter In Foods Of Animal Originmentioning
confidence: 99%
See 1 more Smart Citation
“…In Algeria, Bouhamed, Bouayad, Messad, Zenia, Naim and Hamdi [77] found that Campylobacter was present in 55% of 100 turkey neck skins sampled from three traditional and one modern abattoir located in the country’s middle regions, Algiers, Bouïra, and Boumèrdes. The abattoirs were characterised by a lack of disinfection protocols and sterilisation of equipment, and by the use of dirty uniforms.…”
Section: Prevalence Of Campylobacter In Foods Of Animal Originmentioning
confidence: 99%
“…In Algeria, isolated strains from turkeys showed resistance to tetracycline at 81.3%, ciprofloxacin at 75.0%, and erythromycin at 25.0%. 96.9% of the isolates were multidrug resistant and 18 drug resistance patterns were identified [77]. The authors in the previous study argued that the prudent use of fluoroquinolones contributed to the high resistance rates recorded in ciprofloxacin.…”
Section: Antimicrobial Resistance (Amr) Patterns Of Campylobacter mentioning
confidence: 99%
“…Erythromycin is generally the first drug of choice, but fluoroquinolones and on a smaller scale tetracycline constitutes other options (Szczepanska et al, 2017). Campylobacters become more resistant to antimicrobials and many strains developed the multi-drug resistant (MDR) pattern to multiple medicaments (Bouhamed et al, 2018). Multi-drug resistant campylobacter, particularly against quinolones and erythromycin, has increased globally and this has triggered worldwide alarms, as they are the main antibiotics used for the therapy of campylobacteriosis (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2019 ). Only a few studies have evaluated processors for outcomes related to AMR ( Bouhamed et al. 2018 ; Bridier et al.…”
Section: Discussionmentioning
confidence: 99%